Cardiometabolic multimorbidity in Mexican adults: a cross-sectional analysis of a national survey - Agudelo-Botero, Marcela; Dávila-Cervantes, Claudio A.; Giraldo-Rodríguez, Liliana (Frontiers in Medicine, 2024)
Background Cardiometabolic multimorbidity is a rising phenomenon that has been barely explored in middle-income countries such as Mexico. Objective This study aimed to estimate the prevalence, associated factors, and patterns of cardiometabolic multimorbidity (2 and 3+ diseases) in Mexican adults (≥20 years old) by age group. Methods A cross-sectional and secondary analysis of Mexico’s National Health and Nutrition Survey 2018–2019 was conducted. Information on eight diseases and other sociodemographic and health/lifestyle characteristics was obtained through self-reporting. Descriptive analyses were performed, and multinomial logistic regression models were calculated to identify the variables associated with cardiometabolic multimorbidity. Factor analysis and latent classes were estimated to determine disease patterns. Results The prevalence of cardiometabolic multimorbidity for the total population study was 27.6% (13.7% for people with 2 diseases and 13.9% for people with 3+ diseases). By age group, the prevalence of 2+ diseases was 12.5% in the age group of 20–39 years, 35.2% in the age group of 40–59 years, and 44.5% in the age group of 60 years and older. The variables of depressive symptomatology and having functional limitations (1+) were statistically associated with cardiometabolic multimorbidity in almost all age groups. Patterns of cardiometabolic multimorbidity varied among adults in different age groups. Understanding the behavior of cardiometabolic multimorbidity at various stages of adulthood is a resource that could be used to design and implement intervention strategies. Such strategies should correspond to the population’s sociodemographic, health, and lifestyle characteristics and the specific disease patterns of each age group.